Evaluasi Sumber Daya Manusia Dalam Meningkatkan Mutu Pembelajaran Di Sekolah Dasar Islam Terpadu Insan Mulia Bengkulu - Anggi Santika; Afrizal Syafriantoni; Reska Norda Lesti (Al-Khair Journal : Management, Education, and Law, 2023)
Abstract: The quality of learning at SD IT Insan Mulia Bengkulu is still not optimal, as seen in the results of report cards, and student achievement has not been maximized, this is related to the ability of human resources or teachers in managing classes and the ability of teachers to interact with students. The purpose of this study is to evaluate human resources in improving the quality of learning at SD IT Insan Mulia Bengkulu. Using descriptive qualitative methods. Sources of information from various sources, both online and print media, such as scientific books, scientific articles, both national and international related to the evaluation of human resources in improving the quality of education in Integrated Islamic elementary schools Insan Mulia Bengkulu. The results of the study can be concluded that there are still some teachers who have not been able to mobilize, facilitate, influence, motivate, their students, and have not been able to create conducive learning, the planned planning turns out that the results have not been achieved as planned, and there is still a gap between the plan and the achievement of the goals that have been set, so that there is still a gap in achieving goals with planning in improving the quality of learning. So that researchers can suggest, if you want to improve the quality of learning at SD IT Insan Mulia, then evaluate human resources or teachers in improving the quality of learning through making programs, implementing programs, evaluating and following up on evaluation results.Keywords: Evaluation, Human Resources, Learning QualityÂ Abstrak: Mutu pembelajaran di SD IT Insan Mulia Bengkulu masih belum optimal terlihat hasil nilai raport, dan prestasi siswa belum maksimal, hal ini berkaitan dengan kemampuan sumberdaya manusia atau guru dalam mengelola kelas dan kemampuan guru dalam melakukan interaksi dengan peserta didik. Tujuan dari penelitian ini untuk mengevaluasi sumber daya manusia dalam meningkatkan mutu pembelajaran di SD IT Insan Mulia Bengkulu. Menggunakan metode kualitatif deskriptif. Sumber informasi dari berbagai sumber, baik media online ataupun media cetak. Seperti buku ilmiah, artikel ilmiah, baik nasional maupun internasional yang berkaitan dengan evaluasi sumberdaya manusia dalam meningkatkan mutu pendidikan di sekolah dasar Islam Terpadu Insan Mulia Bengkulu. Hasil penilitian dapat disimpulkan bahwa masih terdapat sebagian guru yang belum mampu menggerakkan, memfasilitasi, mempengaruhi, memotivasi, siswanya, dan belum mampu menciptakan pembelajaran yang kondusif, perencanaan yang telah direncanakan tersebut ternyata hasilnya belum tercapai sesuai rencana, dan masih terjadi kesenjangan rencana dengan pencapaian tujuan yang telah ditetapkan, sehingga masih terjadi kesenjangan pencapaian tujuan dengan perencanaan dalam meningkatkan mutu pembelajaran. Sehingga peneliti dapat menyarankan, jika ingin meningkatkan mutu pembelajaran di SD IT Insan Mulia, maka lakukan evaluasi sumberdaya manusia atau guru dalam meningkatkan mutu pembelajaran melalui membuat program, pelaksanaan program, melakukan evaluasi dan menindaklanjuti hasil evaluasi.Kata Kunci: Evaluasi, Sumber Daya Manusia, Mutu Pembelajaran